Manual on the production and use of live food for aquaculture (FAO, 1996)
The book reviews and summarizes the latest development concerning the production and use of the major live food organisms currently employed in larviculture worlwide. It describes the main production techniques as well as their application potential in terms of their nutritional and physical properties and feeding methods